Beneficial effects of sodium glucose cotransporter 2 inhibitors on left ventricular mass in patients with diabetes mellitus. Issue 11 (21st July 2021) - Kosugi, Daisuke; Inaba, Hidefumi; Kaido, Yosuke; Ito, Saya; Hirobata, Tomonao; Toyofuku, Mamoru; Matsuoka, Takaaki; Inoue, Gen
Abstract: Background: Sodium glucose cotransporter 2 inhibitor (SGLT2i) has recently been suggested to reduce the risk of cardiovascular events. Left ventricular hypertrophy (LVH) is associated with cardiovascular events. Diabetic macroangiopathy is a crucial complication in patients with diabetes mellitus (DM). This study examined the effect of SGLT2i on LVH in patients with type 2 DM (T2DM). Methods: The retrospective cohort study was conducted in consecutive outpatients with T2DM from 2010 to 2020. Left ventricular mass index (LVMI) was used as an indicator of LVH based on echocardiography. The minimum follow‐up period was 1 year. After propensity score‐matching for clinical profiles, patients who underwent annual echocardiography twice for a routine checkup and took SGLT2i were defined to the SGLT2i group, whereas patients without SGLT2 inhibitors were defined to the non‐SGLT2 group. SGLT2i was administered after baseline echocardiography followed by a second examination. Results: LVMI levels in the SGLT2i group (n = 169) significantly decreased from baseline compared with those in the non‐SGLT2i group (n = 169), % changes in LVMI2.7(g/m 2.7 ) in median (interquartile ranges [IQR]) were − 7.7 (−18.7, 2.5) vs −3.6 (−14.3, 5.8), respectively, P = 0.017). In a subgroup analysis, LVMI levels in the patients who had LVH in the SGLT2i group more significantly decreased than those without LVH, % changes in LVMI2.7(g/m 2.7 ) in median (IQR) were −13.5 (−22.1, −2.4) vs −2.8 (−12.6, 9.8), respectively, P < 0.001). Conclusions: SGLT2i treatment was shown to improve LVH in patients with T2DM and may play a pivotal role in the future treatment of diabetic cardiovascular complications. Abstract : Highlights We evaluated Japanese patients with type 2 diabetes mellitus (T2DM) for the effect of sodium glucose cotransporter 2 inhibitor (SGLT2i) on left ventricular hypertrophy (LVH). Left ventricular mass index (LVMI) was used as an indicator of LVH. LVMI levels significantly decreased after administration of SGLT2i. After SGLT2i treatment, LVMI levels in the patients who had LVH significantly decreased compared with patients without LVH. SGLT2i was therefore shown to improve LVH in patients with T2DM. 摘要: 背景: 钠葡萄糖协同转运蛋白2抑制剂(SGLT2i)最近被认为可以降低心血管事件的风险。左心室肥厚(LVH)与心血管事件有关。糖尿病大血管病变是糖尿病患者的重要并发症。本研究观察了SGLT2i对2型糖尿病(T2DM)患者左室肥厚的影响。 方法: 采用回顾性队列研究方法, 对2010 2020年门诊随访的2型糖尿病患者进行研究。超声心动图以左心室重量指数(LVMI)作为左心室肥厚的指标。最短随访时间为1年。在对临床资料进行倾向评分匹配后, 每年进行两次超声心动图常规检查, 服用SGLT2i的患者被定义为SGLT2i组, 而未服用SGLT2i的患者被定义为非SGLT2i组。在基线超声心动图检查后, 服用SGLT2i, 随后进行第二次检查。 结果: 与非SGLT2i组比较, SGLT2i组左心室重量指数显著降低(P=0.017), LVMI2.7(g/m2.7)的中位数(四分位数范围)的变化百分比分别为‐7.7(‐18.7, 2.5)vs ‐3.6(‐14.3, 5.8), P=0.017, 在亚组分析中, SGLT2i组中左室肥厚患者的左心室质量指数较无左心室肥厚的患者明显降低, LVMI2.7(g/m2.7) 中位数的变化百分比分别为‐13.5(‐22.1, ‐2.4)vs‐2.8(‐12.6, 9.8), P<0.001。 结论: SGLT2i治疗可改善T2DM患者的LVH, 并可能在未来糖尿病心血管并发症的治疗中发挥关键作用。